Diagnosis and treatment of osteoporosis in patients with osteoporotic hip fracture: Odkrivanje in zdravljenje osteoporoze pri bolnikih z osteoporoznim zlomom kolka - Krajnc, Mateja; Ivetić, Vojislav (Acta Medico-Biotechnica, 2021)
Purpose: The aim of the study was to determine the prevalence of undiagnosed and untreated osteoporosis cases prior to hip fracture, to determine if there are more patients with diagnosed and treated osteoporosis from model family medicine practices compared to standard family medicine practice patients, and to determine the proportion of patients initiating osteoporosis therapy after discharge from hospital. Methods: We conducted a retrospective, qualitative study at the Department of Surgery, General Hospital of Dr. Jože Potrč Ptuj, Slovenia, using patient records from the period of January 1, 2015 to December 31, 2016, including data analysis of patient discharge letters.Results: The analysis used data from 145 patients, 26 men (17.9%) and 119 women (82.1%). The mean age was 82.7 (±6.8) years. At discharge, 70.4% (81 out of 115) of patients were mobile and 28.3% (41 out of 145) of these were discharged and allowed to return home. The study showed that osteoporosis prior to hip fracture was undiagnosed and untreated in 94.5% (137 out of 145) of cases. Osteoporosis therapy was initiated at discharge in only 7.1% (10 out of 140) of patients, and recommendations to initiate osteoporosis therapy at discharge were provided in 15.0% (21 out of 140). There was no significant difference between model family medicine practice patients (5 out of 91; 5.5%) and patients from standard family medicine practices (8.1%; 3 out of 37) in the proportion of patients treated for osteoporosis prior to hospitalization due to hip fracture (p>0.05).Conclusion: The study concluded that the prevalence proportion of undiagnosed osteoporosis is quite high and that, despite all recommendations and guidelines, management of osteoporotic hip fractures still remains a major challenge at all levels of healthcare.
Keywords: osteoporotic hip fracture; family medicine; regional hospital; osteoporosis